A Single‐Walled Carbon Nanotube Coated Flexible PVC Counter Electrode for Dye‐Sensitized Solar Cells. Issue 2 (23rd December 2013) - Hashmi, Syed Ghufran; Halme, Janne; Ma, Ying; Saukkonen, Tapio; Lund, Peter
<x xml:space="preserve">Abstract</x> A single‐walled carbon nanotube coated PVC substrate is fabricated with a low temperature ink. This substrate exhibits remarkable mechanical durability, impressive charge transfer resistance (2.7 Ω cm2) and similar photovoltaic performance compared to the traditional thermally platinized counter electrodes based dye sensitized solar cell when tested as nonmetallic catalyst loaded metal‐free counter electrode. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>